BIOGEOCHEMICAL CHARACTERISTICS OF DISSOLVED AND PARTICULATE ORGANIC MATTER IN RUSSIAN RIVERS ENTERING THE ARCTIC OCEAN - Lobbes J.M.; Fitznar H.P.; Kattner G. (My University, 2000)
The biogeochemical signature of riverine matter in the Russian Arctic was investigated to establish a background for tracing terrestrial organic material in the Arctic Ocean. Elemental and lignin compositions of particulate and dissolved organic matter (POM, DOM), stable carbon isotope ratios of POM and nutrient concentrations are reported for 12 Russian rivers along 4000 km of coastline. The 12 rivers account for about 43% of the freshwater supply to the Arctic Ocean. Nine rivers drain both tundra and taiga areas and three rivers only tundra. Concentrations of nitrogenous nutrients and phosphate were low, whereas silicate values were generally high with only few exceptions. The concentrations of particulate organic carbon (POC) varied between 25.5 and 291 μmol/L C, contributing 0.4–2.1% to the total suspended sediment (TSS). Dissolved organic carbon (DOC) ranging from 230 to 1006 μmol/L C was on average eight times higher than POC. The concentrations of particulate and dissolved organic nitrogen were similar (ca. 11 μmol/L N) resulting in four times higher C/N ratios in the dissolved fraction (48) compared to the particulate fraction (11). The δ13C ratios were uniform (−25.6 to −27.4‰) and similar in taiga and tundra draining rivers. The exclusively terrestrial component lignin, determined as lignin phenols after cupric oxide oxidation, ranged from 5.6 to 37.6 nmol/L in the particulate fraction and from 34 to 319 nmol/L in the dissolved fraction. The syringyl/vanillyl (S/V) and cinnamyl/vanillyl (C/V) ratios of the particulate and dissolved lignin phenols were significantly correlated with the proportion of tundra and taiga in the drainage areas. This is true despite different formation processes and diagenetic degree of POM and DOM, as evident from acid/aldehyde ratios of vanillyl phenols [(Ad/Al)v]. Export rates were calculated from the carbon and lignin data. The 12 rivers studied transport about 10 × 1012 g of total organic carbon per year into the Arctic Ocean. The largest proportion is discharged by the Yenisey River with about 5 × 1012 g/yr. Total lignin discharge was about 42 × 109 g/yr. The contribution of lignin to the overall carbon flux (0.26% of carbon export) was almost negligible, which does not limit its quality as a quantitative tracer for organic matter fluxes from tundra and taiga regions.